Perbedaan Tingkat Perkembangan Sosial Anak Obesitas dan Tidak Obesitas pada Usia Sekolah: Differences in the Level of Social Development of Obese and Non-Obesity Children at School Age - Ruminingsih, Esri (Jurnal Kebidanan Midwiferia, 2016)
Social development of children at the school marked the expansion of ties with forming a new bond with peers (peer group). Obesity has an impact on the growth and development of children, especially the consequences on the psychosocial aspects because he felt different from the people in general, including creating a sense of lack of confidence, depression , and passive because it is often not involved in the activities undertaken by their peers. The purpose of this research was an analyzed the differenced level of social development ofobese and non-obese childhood at school age in elementary school MIN Karanganom, Klaten. This study was an comparative researsh with cross sectional approach. Techniques using Mann Whitney analysis with significance level of 95%. The number of sampel in this study was taken by usingtotal sampling technique was obtained asa many as 123 students.Indicates that respondents with a middel level of social development as many (53,7%), who haveobesity as many (33,3%). Results of analysis using Mann Whitney obtained p value (0,002) α < (0,05),that mean a significant differences level of social development of obese and non-obese childhood atschool age in Elementary School MIN Karanganom, Klaten. Conclusion:that mean a significantdifferences level of social development of obese and non-obese childhood at school age in ElementarySchool MIN Karanganom, Klaten